Model Pengawasan Internal dan Pemberdayaan Untuk Mendorong Penguatan Moderasi Beragama di Perguruan Tinggi Keagamaan Negeri - Shaleh Shaleh; Elma Haryani; Deni Indrawan; Zaki Sima Fashimado; Yan Suryo Sumirat (Badan Litbang dan Diklat Kementerian Agama RI, 2023)
This research is motivated by the inability of internal audits to encourage the performance of strategic government programs implemented in Islamic State Universities (PTKN). One of the government's priority programs run by PTKN is the program to strengthen religious moderation. This study aims to identify internal control models implemented in tertiary institutions. These supervisory models are then examined for their empowerment potential to encourage the performance of strengthening religious moderation. For this purpose, the researcher empowered the case study qualitative research method by collecting data using observation, interview, and documentation techniques. The data collected was checked for validity using the triangulation technique and analyzed using the Miles, Huberman, and Saldana technique. The results of the research show that: (1) 2 models of internal control have been implemented in tertiary institutions, namely: the partial-thematic internal audit model and the collaborative internal control model; (2) identified 1 (one) audit model that has the potential to be studied further and that in the future it can be applied to tertiary institutions, namely the integrative audit model; (3) models of internal control that tertiary institutions have implemented can be empowered to support and encourage the strengthening of religious moderation and other strategic program.